Multidirectional proton-conducting membrane based on sulfonated big π-conjugated monomer into block copoly(ether sulfone)s. (3rd January 2019) - Wang, Zhan; Su, Yumiao; Li, Minyu; Li, Wenmu
Abstract: The R&D of proton exchange membrane (PEM) with high conductivity and excellent stability is still of significance for the next generation high power density PEM fuel cells. One irreconcilable challenge is that the high proton conductivity realized through high ion exchange capacity (IEC) strategy always gets along with poor membrane stability. To alleviate this contradiction, large-size planar 4, 4'-(5, 11-dihydroindolo[3, 2-b]carbazole-6, 12-diyl)diphenol (DCP) units with highly dense sulfonation were deliberately incorporated into block poly(ether sulfone)s to facilitate the formation of hydrophobic/hydrophilic nanophase-separated structure and multidirectional proton-conducting channels through strong intermolecular π-π interaction and ionic acid-base interaction. In fact, proton conductivity of our PEMs with an IEC of 1.52 mequiv g −1 is up to 248.2 mS cm −1 at 90 °C without compromising its mechanical properties. The novel multi-sulfonated poly(ether sulfone)s could give a guideline for the development of multidirectional proton-conducting membrane. Graphical abstract: Highlights: Multidirectional proton-conducting mechanisms were investigated. The novel PEMs with strong π–π stacked DCP structures suppressed swelling effectively. The strong ionic acid–base interactions in the sulfonated copolymers shortened the distance of proton conduction. The PEMs showed the highest conductivity of 248.2 mS cm −1 at 90 °C.